2002
DOI: 10.1093/humrep/17.2.481
|View full text |Cite
|
Sign up to set email alerts
|

Serum free beta-HCG and alpha-fetoprotein levels in IVF, ICSI and frozen embryo transfer pregnancies in maternal mid-trimester serum screening for Down's syndrome

Abstract: The present data confirm that the overall FPR in the serum screening for Down's syndrome in assisted reproduction pregnancies is high, resulting in unnecessary invasive procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 14 publications
3
21
1
1
Order By: Relevance
“…In our data mean hCG-β levels after frozen cycles were significantly higher than those after fresh cycles regardless of pregnancy outcomes. It is noteworthy that mid-trimester hCG-β levels in pregnancies achieved after frozen cycles are higher than those of fresh cycles [33,34]. The differences in hCG-β levels among these studies could be explained by various factors including day of ET, embryo biopsy, method of fertilization, method of freezing and thawing, media of embryo culture and etiology of infertility, etc.…”
Section: Discussionmentioning
confidence: 95%
“…In our data mean hCG-β levels after frozen cycles were significantly higher than those after fresh cycles regardless of pregnancy outcomes. It is noteworthy that mid-trimester hCG-β levels in pregnancies achieved after frozen cycles are higher than those of fresh cycles [33,34]. The differences in hCG-β levels among these studies could be explained by various factors including day of ET, embryo biopsy, method of fertilization, method of freezing and thawing, media of embryo culture and etiology of infertility, etc.…”
Section: Discussionmentioning
confidence: 95%
“…Several authors have noted elevated second trimester hCG levels following frozen ET when compared to fresh ET (1618), however these studies did not specifically assess rates of first trimester increase. We found that the association of hCG level and type of conception was constant even when we stratified our analysis based on gestational age and absolute hCG concentration, suggesting the difference in hCG rise is already apparent as early as 15 days post-IVF retrieval (and remains unaltered) (Supplemental Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancies conceived by assisted reproduction techniques (ART) have been reported to be associated with changes in the biochemical parameters of screening for DS, leading to an increased false-positive rate (FPR) in the second trimester (1)(2)(3)(4)(5)(6). The effect of ART on first-trimester Down screening, which combines maternal age, nuchal translucency thickness (NT), maternal serum free b subunit human chorionic gonadotropin (fb-hCG), and pregnancy-associated plasma protein-A (PAPP-A), has been examined, but the results have been inconclusive.…”
mentioning
confidence: 99%